СОВЕРШЕНСТВОВАНИЕ ЛОГИСТИЧЕСКОЙ ИНФРАСТРУКТУРЫ ПУТЕМ ПРИМЕНЕНИЯ ТЕХНОЛОГИИ КОНТРЕЙЛЕРНЫХ ПЕРЕВОЗОК В РЕСПУБЛИКЕ КАЗАХСТАН (Промышленный Транспорт Казахстан, 2024)
This article analyzes the current situation in the transport services market of the Republic of Kazakhstan and the need for new logistics solutions. The paper details the technology of piggyback (trailer-on-flatcar) transportation, which is a type of combined transport that merges the advantages of rail and road transport. The author examines the global experience of piggyback systems, specifically the American "TOFC" (piggyback) system. A set of technical, technological, organizational, and regulatory measures necessary for implementing this technology in Kazakhstan is proposed. The article describes the types of piggyback terminals, requirements for specialized rolling stock, the main stages of organizing transportation, as well as issues of liability distribution and tariff calculation. The primary goals and objectives for the development of piggyback transportation are identified.